Analysis of Abamectin Residues in Peach Juice by Absorption Spectrum - Ji, Rendong; Wang, Xiaoyan; Wang, Mahua; Zhang, Yulin; Wang, Shihu; Yang, Dingli; Tang, Yongfeng (Asian Journal of Chemistry, 2014)
In this work, two kinds of simple and precise approaches are developed for the determination of abamectin residues in peach juices based on absorption spectrum. One method focuses on the analysis of the intensity at 219 nm wavelength of original absorption spectra. The other one aims at the technology of calculating the intensity at 223, 249 and 259 nm wavelength of the first derivative of ratio spectra. In addition, both of correlation coefficients are found to be all higher than 0.99. Then the prediction models of abamectin residues were obtained in peach juice with good accuracy. The limit of detection was 0.1377 μg/mL and limit of quantifications was 0.4591 μg/mL in peach juice about the original absorption spectra method, while the minimum value of limit of detection was 0.0285 μg/mL and limit of quantifications was 0.0949 μg/mL about the first derivative of the ratio spectra method. Therefore, they can be suitably applied in the estimation of abamectin residues in peach juice.